Efektifitas edukasi dan konseling faktor risiko hipertensi terhadap peningkatan pengetahuan, sikap dan frekuensi konsumsi natrium pada remaja dengan tekanan darah di atas normal - Mintarsih, Sri Noor; Ismawanti, Zuhria; Susiloretni, Kun Aristiati; Andari, Izzati Hayu; Mardiana, Mardiana; Noer, Etika Ratna (Poltekkes Kemenkes Aceh, 2026)
Background: Hypertension is no longer limited to older adults and increasingly affects adolescents. Behavioral risk factors, such as high sodium intake, high fat consumption, and insufficient physical activity, contribute to an increased risk of hypertension. Limited knowledge and unfavorable attitudes toward hypertension prevention among adolescents may perpetuate unhealthy behaviors, highlighting the need for educational interventions as an early strategy to prevent non-communicable diseases.Objective: This study aimed to determine the effectiveness of education and counselling in improving adolescents’ knowledge, attitudes, and dietary patterns related to hypertension risk factors.Methods: An experimental study using a pretest–posttest control group design was conducted at SMAN 10, Semarang City, from June 19 to July 23, 2025. A total of 29 tenth-grade students with blood pressure >120/80 mmHg were randomly assigned to the intervention (n = 15) and control (n = 14) groups. The intervention consisted of nutrition education and counselling using a booklet entitled “Healthy Living to Prevent Hypertension.” The collected data included knowledge, attitudes, and frequency of sodium-rich food consumption. Data were analyzed using independent t-tests.Results: The mean increase in knowledge (6.6 points) and attitude (2.1 points) scores was higher in the intervention group (p=0.109; p=0.333), and the mean frequency score of sodium-rich food consumption decreased by 3 points (p=0.115) compared to that in the control group. However, these differences were not statistically significant. Based on effect size, the intervention showed a greater tendency to reduce the frequency of sodium-rich food consumption (12.9%) than to improve knowledge (10.5%) and attitudes (3.7%).Conclusion: Nutrition education and counselling have the potential to improve knowledge, attitudes, and sodium-related dietary patterns among adolescents, although the results were not statistically significant in this study. This intervention shows promise as a preventive strategy for hypertension in adolescents.